Longevity Recipe - Lifestyle Influences on the Quantity and Quality of Life - Katarzyna Piotrowicz; Hubert Piotrowicz; Jacek Kurzeja; Agnieszka Bajkacz; Wojciech Kraśnik; Olga Jankowska; Anna Rogala; Joanna Osmólska (Journal of Education, Health and Sport)
Introduction and Purpose. For many years, people have been fascinated by the question of how to achieve a long and healthy life, seeking a recipe for longevity. Our lifestyle can play a significant role in this. The aim of this review is to enhance public awareness of longevity and to emphasise the consequences of our daily habits. Materials and Methods. A literature review was carried out using the PubMed database, searching for the most recently published scientific sources. State of Knowledge. The review details the impact of individual lifestyle elements on quantity and quality of life. The benefits of physical activity were discussed, including the amount of exercise necessary per week to reduce mortality risk, and the most efficacious sport disciplines for health promotion. It also emphasises the significance of dietary habits and the role of phytochemicals. Additionally, it addresses the following questions: Does consuming small amounts of alcohol prolong life? What is the extent of the damage caused by smoking? How can stress and sleep be managed? Why are social relationships an important protective element? Finally, it considers whether there is a cure for longevity. Summary. A holistic approach that encompasses a sufficient level of physical activity, proper nutritional habits and the maintenance of a healthy body weight can contribute towards the attainment of longevity. Conversely, factors such as smoking, alcohol consumption, poor stress or sleep management and loneliness can have a negative effect on life expectancy. A search is underway for anti-aging pharmacological compounds that are both efficacious and safe.